Development of Micro Hydro Power Center Miniature Media in Science Learning for Elementary School - Ristiana Dyah Purwandari; Desi Putrianasari; Abdul Haris Mulyadi; Vina Zahra Alkharis; Vira Zahra Alkharis (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
The Miniature Micro Hydro Power Center (MHPC) media is a development of learning media. The use of MHPC miniature learning media can improve critical thinking skills for elementary school students in Indonesia. The way the MHPC miniature works is similar to the original, namely the Karekan MHPC (MHPC in the Karekan Area). Research objective: to create a miniature MHPC media product and test the effect of using miniature MHPC on critical thinking skills. This study uses the ADDIE Research and Development model. Research methods: 1. product validation test developed by science content experts (1 lecturer), media validation by five experienced teachers, technicians, nine practitioner teachers as users; 2. Quasi Experiment, to test the effect of the use of miniature MHPC on critical thinking skills, involving 102 students of class V (sample of 4 classes from 4 schools, consisting of 2 experimental classes and two control classes) from 7 schools (as population) in the Kihajar Dewantara cluster, North Purwokerto District, Banyumas Regency, namely SDN Grendeng 1, 2, 3, and 4. The data from the posttest were tested for normality, homogeneity, and an independent sample T-test using SPSS 2022. The results of the study: the validation results of science content experts, experienced teachers, technicians, and nine practitioner teachers (using CVI) gave the product a > 85 with the comment "MHPC miniature media is suitable for use in learning". The results of the normality and homogeneity tests obtained significant values of 0.09 and 0.6, where sig>0.05. The results of the Independent Sample T-test showed a positive effect of the use of MHPC miniature media on critical thinking skills in the experimental class compared to the control class, which only used MHPC Kareka video media; a significance value of 0.00<0.05 was obtained. Skepticism: The results of the development of MHPC's miniature products can be used in science learning and have a positive effect on students' critical thinking skills.